1997
DOI: 10.1023/a:1026489104188
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3/CPP32-like activity is not sufficient to mediate apoptosis in an IL-2 dependent T cell line

Abstract: CTLL cells undergo apoptosis when cultured in the absence of IL-2. The IL-1beta-converting-enzyme (ICE)/ caspase family has been implicated as an integral component of some forms of apoptosis. Numerous members of the caspase family have been identified, and it appears as if caspase-3/CPP32 plays a critical role. Previously we demonstrated that ICE/caspase-1 expression increases in CTLL cells during apoptosis; however, inhibition of ICE activity did not abrogate apoptotic death. The purpose of this report is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…In these studies, apoptosis was monitored by metabolism of the dye AlamarBlue (41). Recently, Vasilakos et al (42), demonstrated that cell death data obtained with AlamarBlue correlated well with data obtained in the same experiment by monitoring trypan blue exclusion as an index of cell viability. In addition, positive correlation between AlamarBlue and several other parameters of apoptosis, such as caspase-3 activation, DNA laddering, and nuclear condensation, were demonstrated.…”
Section: Pp2a Competes As a Substrate In Two Caspase-3 Assay Systems-mentioning
confidence: 54%
“…In these studies, apoptosis was monitored by metabolism of the dye AlamarBlue (41). Recently, Vasilakos et al (42), demonstrated that cell death data obtained with AlamarBlue correlated well with data obtained in the same experiment by monitoring trypan blue exclusion as an index of cell viability. In addition, positive correlation between AlamarBlue and several other parameters of apoptosis, such as caspase-3 activation, DNA laddering, and nuclear condensation, were demonstrated.…”
Section: Pp2a Competes As a Substrate In Two Caspase-3 Assay Systems-mentioning
confidence: 54%
“…Caspases 3 and 7 had very potent IRS-1-degrading activity, and caspase 10 had significant but weaker IRS-1-degrading activity. To determine whether caspases 3 and 7 mediated hypoxia-induced cleavage of IRS-1 in cells, we incubated hypoxic cells with Z-DEVD-fmk, an inhibitor of caspases 3 and 7 (50). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…41 ± 44 This suggests that this pathway is still activated in the cell but it is not the pathway that actually kills the cell, perhaps because it is not sufficient to mediate apoptosis in this metabolic state, as it has already been suggested in other cell lines. 45 Alternatively, caspase 3 may be activated by a caspase 1-independent pathway, also involved in the activation of LDNase II. This question is under current investigation.…”
Section: Discussionmentioning
confidence: 99%